Measuring Multi-Dimensional Poverty Analysis in Nepal (Research Nepal Journal of Development Studies, 2018)
This study measures the Multi-Dimensional Poverty of the poverty alleviation fund intervention program districts of Nepal. This study uses quantitative only non-experimental, descriptive and exploratory study/survey design applying multi-stage Cluster Random Sampling method. At 5% margin of error and 95% confidence level sample size of 2,660 households from 14 districts (two districts from each of seven provinces) is determined as representative for the study. The study finds that Multi-Dimensional Poverty Index (MPI) for the study population is slightly higher (0.133) than that of national level (0.127) (NPC, 2018). The rational reason is that the current study was based on PAF households only or economically it is homogeneous population. People living in three different places of residence (urban (0.117) and hill (0.116) found to have better quality of life as compared to corresponding other places (Rural (0.153), Mountain (0.162) and Terai (0.138)). Despite having low human development index (NPC, 2014), provinces No.7 recorded the lowest MPI value (0.084), which is urgently needed to be investigated again. By caste/ethnicity, other categories (e.g., Marwadi, Bangali, Sikh. Jain, Panjawi among others) found lowest poverty level (0.064), followed by Brahmin/Chhetri) (0.069). The highest proportion of headcount ratio (51.5) is noticed in Province No. 2. The gravity of poverty is found high among the Muslim community (44.6). One in every four households (22.9 percent) has the likelihood of being vulnerable to poverty. Households situated in Province No.1 are more vulnerable to poor as compared to population from other provinces.